Strategi Guru dalam Meningkatkan Keterampilan Sains Menggunakan Media Berbasis Praga pada Anak Usia Dini - Hamdani, Muh; Muhajirin, Muhammad; Marzoan, Lalu; Yulia, Neni (Universitas Mataram, 2020)
Science is knowledge that is currently believed to be a tool to explain phenomena that occur in everyday life. However, in delivering science to students, there are often obstacles, especially for students in Early Childhood Education (PAUD). The purpose of this community service activity is to help Early Childhood Education partners in North Lombok Regency in solving problems experienced by partners, namely limited knowledge and experience regarding teacher strategies in developing science skills, especially using media based on props for children and the difficulty of teachers in conveying science phenomena to PAUD students. The solution to this problem is to hold training in developing skills and simple science experiment experiences for Early Childhood education teachers using media based on props. The method of implementing this community service activity consists of training methods, mentoring, and discussions that are carried out directly. Community service that is carried out can improve the skills of teachers in improving simple science skills in Early Childhood students. In the future, in order to maximize the understanding and interest of PAUD students in science, it is necessary to provide knowledge and/or stimulus activities that stimulate students' interest gradually, especially themes that are closely related to everyday life